How functional traits, herbivory, and genetic diversity interact in Echinacea: implications for fragmented populations. Issue 7 (1st July 2015) - Kittelson, Pamela M.; Wagenius, Stuart; Nielsen, Reina; Qazi, Sanjive; Howe, Michael; Kiefer, Gretel; Shaw, Ruth G.
Abstract : Habitat fragmentation produces small, spatially isolated populations that promote inbreeding. Remnant populations often contain inbred and outbred individuals, but it is unclear how inbreeding relative to outbreeding affects the expression of functional traits and biotic interactions such as herbivory. We measured a suite of 12 functional traits and herbivore damage on three genotypic cross types in the prairie forb, Echinacea angustifolia : inbred, and outbred crosses resulting from matings within and between remnant populations. Inbreeding significantly affected the expression of all 12 functional traits that influence resource capture. Inbred individuals had consistently lower photosynthetic rates, water use efficiencies, specific leaf areas, and had higher trichome numbers, percent C, and percent N than outbred individuals. However, herbivore damage did not differ significantly among the cross types and was not correlated with other leaf functional traits. Leaf architecture and low physiological rates of the inbred compared to outbred individuals imply poorer capture or use of resources. Inbred plants also had lower survival and fitness relative to outbred plants. Our results show that inbreeding, a phenomenon predicted and observed to occur in fragmented populations, influences key functional traits such as plant structure, physiology and elemental composition. Because of their likely role in fitness of individuals and ecological dynamics plant functional traits can serve as a bridge between evolution and community or ecosystem ecology.